2011
DOI: 10.1155/2011/939148
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hepatitis B Virus in a Chronic HBV-Infected Patient over 2 Years

Abstract: Mutations in full-length HBV isolates obtained from a chronic HBV-infected patient were evaluated at three time points: 1 day, 6 months, and 31 months. While 5 nucleotides variation, and an 18 bp deletion of preS1 have been kept in during at least the first two years, C339T mutation occurring in the hydrophilic region of HBsAg and T770C that caused polymerase V560A substitution were the new point mutations found existing in sequenced clones of the 3rd time point. Internal deletion of coding region obviously ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Of the 68 SNVs identified by BAsE-Seq in S7.1, 56 confer changes in amino acid sequence, while the other 12 are silent substitutions (Table S4 in Additional file 1 ). Among the non-synonymous variants, seven are nonsense mutations (one in the open reading frame (ORF) for the HBV C protein, one in the ORF for X protein, and five in the ORF for S protein) and one is a mutation in the stop-codon of the C gene that extends the ORF by six amino acids (Table S4 in Additional file 1 ); most of these mutations have been previously described [ 42 - 44 ] or exist in sequences from GenBank. Five of the nonsense mutations are located near the end of their ORFs and consequently may reduce or alter the expression or activity of the expressed proteins rather than abolishing expression altogether.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 68 SNVs identified by BAsE-Seq in S7.1, 56 confer changes in amino acid sequence, while the other 12 are silent substitutions (Table S4 in Additional file 1 ). Among the non-synonymous variants, seven are nonsense mutations (one in the open reading frame (ORF) for the HBV C protein, one in the ORF for X protein, and five in the ORF for S protein) and one is a mutation in the stop-codon of the C gene that extends the ORF by six amino acids (Table S4 in Additional file 1 ); most of these mutations have been previously described [ 42 - 44 ] or exist in sequences from GenBank. Five of the nonsense mutations are located near the end of their ORFs and consequently may reduce or alter the expression or activity of the expressed proteins rather than abolishing expression altogether.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations at this region may directly influence HBV infection and liver disease progression. Pre-S deletion was observed in chronic hepatitis B infection, fulminant hepatitis B, acute hepatitis B and HCC [49][50][51][52][53][54][55][56][57][58] . Several crosssectional studies have shown an association between pre-S mutation and HCC [59][60][61] .…”
Section: Pres1/s2/s Orfmentioning
confidence: 99%